EVALUATION OF THE ADVERSE OUTCOMES OF PARACETAMOL IN HOSPITALIZED PAEDIATRIC PATIENTS – A SINGLE CENTRE STUDY - M, Swetha; RAVI KUMAR C; S, Vijaya Kumar; Ls, Manigandan; Vivean, Priya Rajam (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Paracetamol is one of the effective and well-tolerated drugs by pediatrics and adults in therapeutic doses. The purpose of this study was to examine whether therapeutic doses of acetaminophen are associated with adverse outcomes in hospitalized pediatrics patients. Methods: Thirty children of both sexes aged 6-14 years were enrolled in a single-center, parallel-group study design. Therapeutic doses according to the body weight of neonates and children can be administered in hospital settings. The statistical analysis was performed using SPSS software (version 17.0). Results: This study showed mean±standard deviation (SD) of age in cases and controls were observed to be 8.47±2.980 and 8.75±2.849, where the p=0.66 which is statistically not significant. The body mass index was observed to be 12.40±3.179 and 10.33±2.267 are statistically significant. The mean±SD of cases and controls were found to be 29.10±13.42 and 27.10±8.17. There is a slight increase in the mean serum glutamic oxaloacetic transaminase levels in cases when compared to control groups. The mean serum glutamic-pyruvic transaminase levels slight increases in cases, when compared to control groups were 26.18±48.94 and 24.36±5.92. Conclusion: These findings conclude that, paracetamol is not causing hepatotoxicity, hematological, and nephrotoxicity. Even in supratherapeutic dosing in 25% of the study population we did not find any adverse effects, whose therapeutic level is above 20 μg/ml up to 30 μg/ml. Though standard, recommended therapeutic doses of paracetamol were prescribed in all study population 25% of children showed supratherapeutic levels, which did not show clinical or biochemical signs of toxicity. Keywords: Therapeutic levels, SPSS, Pediatrics, Age, Toxicity.